PUBLIC INTENTION IN BUYING CASH WAQF LINKED SUKUK: MODIFICATION OF THEORY OF REASONED ACTION (TRA) - Neni Sri Wulandari; Yoga Tantular Rachman; Mega Rachma Kurniaputri (Universitas Airlangga, 2022)
Many people only know that waqf is only in the form of land assets, even though today, there is the latest innovation in waqf through Cash Waqf Linked Sukuk to build social infrastructure such as building hospitals. However, CWLS experiences growth every year. This study aims to analyze the public's intention to buy Cash Waqf Linked Sukuk through the Theory of Reasoned Action and also to determine the effect of religiosity on attitudes. Using the causality method, this study uses primary data through questionnaires distributed online to Indonesian Muslim residents over 18 years old who know the Cash Waqf Linked Sukuk program and understand the CWLS program. This study uses Structural Equation Modeling - Partial Least Square to analyze the data. This study found that religiosity had a positive and significant effect on attitudes. In addition, it was also found that subjective attitudes and norms have a positive and significant influence on people's intentions to buy cash waqf-linked Sukuk waqf. The implication of this research is to be the reference for regulators in conducting the study and also to give information about CWLS to the community. The discussion about Cash Waqf Linked Sukuk in Indonesia is still limited; therefore this study was conducted to enhance people's knowledge.